Batik as a craft teaching-learning medium To preserve values of local wisdom in elementary schools in Bantul, Indonesia - Purwastuti, Lusila Andriani (Universitas Negeri Yogyakarta, 2022)
Education is required to give earnest attention to the development of Indonesian people in all dimensions. This is in line with education as the main vehicle in nation and character building. The whole development of its dimensions (arrangement of nature, the characteristics of nature, and the position of nature) can only be done if humans since the beginning of its birth have been educated to the actualization of these potentials. Education would give a real and significant contribution in supporting the development of the nation's character as a whole that become a big agenda for Indonesia. The research approach used in this research is qualitative descriptive. This research took place in SendangsariPrimary School, Pajangan, Bantul, Yogyakarta. The data were obtained by observation, interview, and documentation. The data analysis includes data reduction, classification, verification, and conclusion. The validity of data used triangulation. The research concluded that local wisdom values contained in batik can be identified as follows: the value of honesty, patience, perseverance, cooperation, tolerance, democratic, hard work, patience, religious, virtue, inner and outer well-being, the scientefic value (mixing colors in batik) patient, honest, loving environment, patriotism, creative and innovative. SD Sendangsari has been carrying out thematic-integrative character education based on local wisdom.